Peran Hygiene Industri dalam Mencegah Penyakit Akibat Kerja: Systematic Literature Review - Hafizah Hafni Siregar; Nabiila Annaufa; Mutiara Ayu Situmorang; Abdurrozaq Hasibuan (Media Gizi Kesmas, 2026)
Background: Occupational hygiene is a fundamental discipline in workplace health management that safeguards workers from Work-Related Illnesses (WRI) by systematically anticipating, recognizing, and controlling environmental hazards, and evaluating and controlling risk factors in the workplace. Exposure to physical, chemical, biological, ergonomic, and psychosocial hazards can lead to health issues among workers and reduce workplace productivity. Objectives: This study aims to systematically review the role of industrial hygiene in preventing OWDs across various industrial sectors, as well as to identify types of hazards, risk factors, and effective control strategies. Methods: A systematic literature review was conducted using the Google Scholar, Garuda, and SINTA databases with the keywords "industrial hygiene," "occupational health," "work-related illnesses," "workplace safety," and "good health and well-being." The selected articles were journals in Indonesian and English published between 2020 and 2025 and were available as open access. Results: synthesis of the reviewed literature identified that the most prevalent occupational hazards encompass excessive noise, airborne dust, toxic chemicals, thermal extremes, whole-body vibration, poor ergonomic conditions, and psychosocial stressors. Evidence has demonstrated that applying industrial hygiene principles encompassing engineering and administrative controls, appropriate use of Personal Protective Equipment (PPE), and systematic workplace surveillance substantially lowers the occurrence of work-related illnesses and strengthens workers' engagement in Occupational Health and Safety (OHS) practices. Conclusion: The findings affirm that industrial hygiene is indispensable for sustaining a safe, healthy, and productive work environment. Embedding a holistic and continuously evaluated industrial hygiene program is imperative for curbing the burden of work-related illnesses and elevating OHS performance standard of a comprehensive and sustainable industrial hygiene program is necessary to minimize the risk of work-related illnesses and improve occupational safety and health (OSH) standards in the workplace.